NONENZYMATIC GLYCOLISATION AND GINGIVAL TISSUES: A REVIEW - Bozhinov, Angelina Sredovska; Nakova, Marija (Journal of Morphological Sciences; Vol 5 No 1 (2022): JMS, 2022)
Periodontal diseases are multifactorial conditions caused by infection with pathogenic bacteria and inflammation of tissue. Nonenzymatic glycolisation play a key role in treatment of periodontitis because of the many scientific evidence that advanced-glycation end products can modify many metabolism pathways that can change way of gingival tissue inflammatory and tissue damages. There is no direct evidence for the presence of AGEs in the periodontal ligament but, valuable results that are based on the studies in chronic periodontal patients support a potential role for protein glycation in the aetiology and severity of this disease. This study highlights the need for further investigation on the presence of AGEs in the periodontal tissues and the pathogenic mechanisms underlying periodontal diseases in order to develop prevention and treatment modalities for this dysfunction. Keywords: Nonenzymatic glycolisation, AGEs, RAGEs, Periodontitis, gingival tissue. https://doi.org/10.55302/JMS2251152b